2017
DOI: 10.1136/annrheumdis-2017-211663
|View full text |Cite|
|
Sign up to set email alerts
|

Survival in adults and children with systemic lupus erythematosus: a systematic review and Bayesian meta-analysis of studies from 1950 to 2016

Abstract: After a period of major improvement, survival in SLE has plateaued since the mid-1990s. In high-income countries, 5-year survival exceeds 0.95 in both adults and children. In low/middle-income countries, 5-year and 10-year survival was lower among children than adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
119
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 42 publications
7
119
0
8
Order By: Relevance
“…The 5‐year and 10‐year survival rates were 96.9% and 95.5%, respectively, in our cohort with SLE, which are slightly higher than those reported in previous meta‐analyses but similar to those previously reported in Hong Kong (97% at 5 years and 93.7% at 10 years) and Shanghai (98% at 5 years) . However, because mortality in SLE varies according to not only the study populations’ characteristics, such as ethnicity and socioeconomic status, but also according to the study design and setting, it needs to be validated whether South Korean patients with SLE have a favorable outcome compared with those from other countries. Infection and active SLE are the leading causes for death in patients with SLE worldwide, and this notion is in line with our study's results.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The 5‐year and 10‐year survival rates were 96.9% and 95.5%, respectively, in our cohort with SLE, which are slightly higher than those reported in previous meta‐analyses but similar to those previously reported in Hong Kong (97% at 5 years and 93.7% at 10 years) and Shanghai (98% at 5 years) . However, because mortality in SLE varies according to not only the study populations’ characteristics, such as ethnicity and socioeconomic status, but also according to the study design and setting, it needs to be validated whether South Korean patients with SLE have a favorable outcome compared with those from other countries. Infection and active SLE are the leading causes for death in patients with SLE worldwide, and this notion is in line with our study's results.…”
Section: Discussionsupporting
confidence: 82%
“…A recent meta‐analysis demonstrated that 5‐year survival of patients with SLE in high‐income countries exceeded 95% in 2008‐2016, and the overall survival has reached a plateau since the mid‐1990s . The 5‐year and 10‐year survival rates were 96.9% and 95.5%, respectively, in our cohort with SLE, which are slightly higher than those reported in previous meta‐analyses but similar to those previously reported in Hong Kong (97% at 5 years and 93.7% at 10 years) and Shanghai (98% at 5 years) . However, because mortality in SLE varies according to not only the study populations’ characteristics, such as ethnicity and socioeconomic status, but also according to the study design and setting, it needs to be validated whether South Korean patients with SLE have a favorable outcome compared with those from other countries.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Systemic lupus erythematosus (SLE) is a chronic autoimmune disease of unknown etiology characterized by the presence of antinuclear autoantibodies and inflammation in a wide spectrum of organs . The survival of SLE patients has plateaued since the middle 1990s . To date, anti–double‐stranded DNA (anti‐dsDNA) antibody titration, best achieved with the standard Farr assay, has been used to monitor global disease activity and SLE renal involvement .…”
Section: Introductionmentioning
confidence: 99%
“…2017; Paley, Strand, & Kim, 2017;Tektonidou, Lewandowski, Hu, Dasgupta, & Ward, 2017). Previous studies have identified that the etiology of SLE is multifactorial, and genetic predisposition and environmental factors both have critical roles in its pathogenesis (Moulton et al, 2017;Teruel & Alarcón-Riquelme, 2016;Tsokos, Lo, Reis, & Sullivan, 2016).…”
mentioning
confidence: 99%